To End With the Judgement of the Canon - Salcido, Miroslava (2025)
Introduction: From the character of the manifesto and in dialogue with other writings, the following text postulates the relationship between women’s thinking, writing, philosophy and art as axes of what the author calls ‘life as literary achievement’. Development: This relationship is understood as a position taken with respect to the theological norm of the canon as a discursive strategy, proposing for the Academy another type of writing in favor of the knowledge of the body and otherness versus the enemy otherness. The latter is part of a patriarchal and colonialist discourse that has denied women their place, not only in art, but also in discourse and history. Conclusion: The text advocates overcoming the judgment imposed by the canon on women’s writing and highlights the importance of a feminist intellect within academia.